ANALISA PENGARUH ELECTROLESS PLATING ABU DASAR BATU BARA SEBAGAI PENGUAT KOMPOSIT MATRIKS LOGAM TERHADAP PRODUK REAKSI YANG TERBENTUK PADA PERMUKAAN ABU DASAR BATUBARA - santoso, edi; Seputro, Harjo; Himawan, Eka Puji (JHP17 (Jurnal Hasil Penelitian), 2016)
An electroless plating process that does not use electric current in the coating process. Coatings that occurs due to the reaction of reduction and oxidation of [ermukaan objects, thus forming a layer of metal derived from the metal salt. Because it does not use an electric current in the electron exchange coating process happens more slowly. The purpose of this study is to see the reaction products formed on the surface of coal bottom ash results electroless plating which is affected by variations in the weight of aluminum and temperature oxidation by testing the SEM-EDX. Results of SEM-EDX will be the reaction products formed by using statistical software version PCPDF WIN 2:01. From the test results SEM-EDX with magnesium weight variation and temperature variation affects the oxidation Wt%-forming elements in it but does not affect the elements formed where for all specimens produce similar reactions, namely Aluminium Silicate Al2SiO5.Keywords: Composites, electroless plating, the reaction products formed